A Vatican Encyclical and the Abu Dhabi Declaration - Specker, Tobias (South Asian Journal of Religion and Philosophy (SAJRP), 2023)
The encyclical Fratelli Tutti rarely mentions explicitly the encounter between religions. Nevertheless, it is profoundly marked by the effort of mutual understanding between religions and provides important new impulses for interreligious dialogue. This article examines the dialogical structure of the encyclical and analyses central themes that the encyclical shares in common with the Abu Dhabi Declaration. These are, in particular, a theology of alterity, a decentralized ecclesiology and an anthropology of social connectivity. Finally, the extent to which these papal initiatives resonate in the Islamic context is examined.